Idiopathic Intractable Diarrhoea Leading to Torsade de Pointes - Kyriacos Mouyis; Darlington Okonko; Constantinos G. Missouris (Case Reports in Cardiology)
An 81-year-old lady was admitted to our hospital with a 3-year history of noninfective diarrhoea and recurrent syncopal events over the last 3 months. Her initial electrocardiogram (ECG) revealed trigeminy and prolonged QTc interval. She had a structurally normal heart with no coronary artery disease. Investigations revealed low potassium at 3.0 mmol/L. Sigmoidoscopy and colonoscopy suggested a possible diagnosis of diverticulitis. Soon after admission she had an unresponsive episode with spontaneous recovery. Telemetry and Holter analysis confirmed multiple episodes of polymorphic ventricular tachycardia (Torsade de Pointes). Following electrolyte supplementation the episodes of polymorphic VT improved. Due to the protracted nature of the diarrhoea, the recurrent syncopal events, and recurrent hypokalaemia documented over recent years, an Implantable Cardioverter Defibrillator (ICD) was sanctioned by the multidisciplinary team (MDT). In summary, chronic diarrhoea may result in life threatening polymorphic VT due to hypokalaemia and QTc prolongation. In these patients an ICD may be considered.